ENHANCING SPOKEN ENGLISH SKILLS FOR NATIVE SPEAKERS OF BAHASA INDONESIA - Al-Amin; Ermy Dikta Sumanik; Ekha Sri Sugiarti; Listian Indriyani Achmad; Eyad Saleh Bani-Domi (International Journal of Teaching and Learning, 2023)
In this study, the aim was to enhance the spoken English skills of native speakers of Bahasa Indonesia. A group of 50 participants was selected to undergo a comprehensive language learning program. The methodology included structured formal lessons, regular practice, diverse language learning tools, continuous feedback, and cultural immersion experiences. The results were highly promising. Participants demonstrated a significant 70% reduction in pronunciation challenges, reflecting the effectiveness of targeted pronunciation training. Additionally, there was a notable 65% increase in fluency, underscoring the impact of regular practice and real-life exposure to English. A remarkable 75% expansion of vocabulary indicated the success of incorporating diverse language learning tools. An impressive 80% boost in confidence was attributed to the combination of structured learning and practical experience. Furthermore, a 70% improvement in cultural competence highlighted the value of cultural immersion experiences. The findings suggest that a well-structured approach is highly effective in enhancing spoken English skills. Such proficiency is crucial in today's globalized world, opening doors to personal and professional growth. Educators and learners alike can draw on the insights provided by this research to improve spoken English skills among native speakers of Bahasa Indonesia. This study contributes to the broader understanding of language acquisition and proficiency and the role of cultural immersion in language learning.